Hereditary haemorrhagic telangiectasia and pulmonary arterio-venous malformations in pregnancy: A case series - Katie Lane; Elise Gilbertson; Sophie Poulter (Obstetric Medicine, 2026)
Hereditary haemorrhagic telangiectasia (HHT) is an autosomal dominant disorder affecting approximately 1 in 5000–8000. Pregnancies complicated by HHT are high risk, and many women are advised to give birth in tertiary centres. There is a 1% mortality rate and 2.6% to 6.8% severe maternal complications, though interpretation is limited by small datasets and frequent inclusion of undiagnosed or unscreened patients. We describe 10 pregnancies in six women with HHT managed at Sunshine Coast Health between 2018 and 2024. Four women had pulmonary arteriovenous malformations: one treated preconception, two embolised in the second trimester, and one diagnosed postpartum after no antenatal screening. Three women underwent preconception pulmonary screening. No pregnancies required early delivery for HHT or experienced HHT-related intrapartum complications. These findings suggest that with appropriate screening, planning and multidisciplinary management most women with HHT can be safely managed in pregnancy when supported remotely by tertiary services.